Development of Triamcinolone Acetonide Nanocrystals for Ocular Administration - María Lina Formica; Hamoudi Ghassan Awde Alfonso; Alejandro Javier Paredes; María Elisa Melian; Nahuel Matías Camacho; Ricardo Faccio; Luis Ignacio Tártara; Santiago Daniel Palma (MDPI AG, 2023)
Triamcinolone acetonide (TA) is a powerful anti-inflammatory drug used in the treatment of inflammatory ocular disorders; however, its poor aqueous solubility and ocular anatomical barriers hinder optimal treatment. The aim of this work was to obtain triamcinolone acetonide nanocrystals (TA-NC) to improve ocular corticosteroid therapy. Self-dispersible TA-NC were prepared by the bead milling technique followed by spray-drying, exhaustively characterized and then evaluated in vivo in an ocular model of endotoxin-induced uveitis (EIU). Self-dispersible TA-NC presented an average particle size of 257 ± 30 nm, a narrow size distribution and a zeta potential of −25 ± 3 mV, which remained unchanged for 120 days under storage conditions at 25 °C. In addition, SEM studies of the TA-NC showed uniform and spherical morphology, and FTIR and XRDP analyses indicated no apparent chemical and crystallinity changes. The subconjunctival administration of TA-NC in albino male white rabbits showed no clinical signs of ocular damage. In vivo studies proved that treatment with self-dispersible TA-NC alleviated the inflammatory response in the anterior chamber and iris in EUI rabbit eyes. Dispersible TA-NC are a promising approach to obtaining a novel nanometric TA formulation for ocular disorders.